2019
DOI: 10.1016/j.jenvrad.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study on the technical aspects of sampling, transporting and measuring radon-in-water

Abstract: The European Commission's Joint Research Centre organizes proficiency tests (PT) on radon-in-water measurements. In order to optimize sampling, transport and measurement methods many tests and small scale proficiency tests have been performed. The waters from natural springs, wells were sampled on-site in glass bottles then transported cooled to the JRC and collaborating laboratories. For the material characterization standard measurement methods based on gamma-ray spectrometry, emanometry and liquid scintilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…As already confirmed by experience in the literature, measurements of radon activity concentrations in different natural water bodies like rivers, springs, groundwater, surface waters and drinking waters on samples are affected by some technical difficulties with respect to radon measurements in other matrices [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…As already confirmed by experience in the literature, measurements of radon activity concentrations in different natural water bodies like rivers, springs, groundwater, surface waters and drinking waters on samples are affected by some technical difficulties with respect to radon measurements in other matrices [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Water was collected in polyethylene terephthalate (PET) bottles. It was observed that polyethylene terephthalate (PET) has generally lower radon loss during storage 12,13 than high density and low-density polyethylene 14 . The material and the sealing are compliant with ISO 13164–1:2013 15 and ISO 13164-3:2013 16 concerning principles to be adopted in water sampling, storage, and transportation.…”
Section: Methodsmentioning
confidence: 99%
“…The emanation sources were already tested in radonin-water measurements where elevated radon activity concentration had to be produced in a low volume (0.2-1 L) container [6]. The emanation sources were placed in an LDPE foil and immersed in a 1-L heat shock resistant borosilicate glass bottle with a gas-tight but flexible screw cap designed for volatile organic material storage.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the MetroRadon project objectives, JRC had to take the priorities within its own work program into account, which includes radon-in-water measurement [6][7][8]. On that basis, we set three main goals for the radon emanation source preparation at JRC-Geel.…”
Section: Introductionmentioning
confidence: 99%